Veliki angleško-slovenski slovar OXFORD-DZS dokončan - Hočevar, Mojca M. (Mostovi (Ljubljana), 2006)
The largest and most comprehensive English-Slovene dictionary for Slovenian users is presented, the second volume of which was published at the end of 2006. The dictionary is the first Slovenian corpus dictionary, prepared by means of the Oxford-Hachette English-French Dictionary, the Fida Slovenian text corpus and other sources. The netries and translation equivalents were independently selected for Slovene, and the Comprehensive English-Slovene Dictionary by Anton Grad, Ružena Škerlj and Nada Vitorovič was not used among the sources.
Keywords: angleščina; ocene in poročila; slovarji; slovenščina; Veliki angleško-slovenski slovar OXFORD-DZS